Parenting of Industrial Workers: The Impact of Emotional Social Development of Early Childhood - Yusuf, Ali; Budi Wiyono, Bambang; Hardika; A., Rasyid Al Atok (International Journal of Psychosocial Rehabilitation, 2020)
The pattern of parenting in the current era is the foundation of the child’s maturity. Children who get parenting from parents on an ongoing basis will foster children’s social-emotional. This is different from the condition of children of industrial workers. Parents of industrial workers’ with limited time, lack of education, and family economic needs have an impact on children’s emotional social development. Therefore, this study aims to determine the parenting patterns of the parents of industrial workers, and the impact of emotional social development of early childhood in Driyorejo Sub-District, Gresik Regency, East Java, Indonesia. This research was conducted using a qualitative research design, with 30 respondents as industrial workers. Data analysis uses an interactive model, namely, data collection, data reduction, data display, and conclusion drawing. The findings of this study indicate that parenting has an impact on children’s psychological development, such as levels of education, family economy, pampering children, and leaving to stay at grandma’s house. They become an inhibiting factor for children’s social-emotional development. Therefore, this research is important to provide information to parents and schools to provide a large portion in the pattern of early childhood care in the golden period.